2023
DOI: 10.1177/26317745221149626
|View full text |Cite
|
Sign up to set email alerts
|

Palliative therapy for malignant gastric outlet obstruction: how does the endoscopic ultrasound-guided gastroenterostomy compare with surgery and endoscopic stenting? A systematic review and meta-analysis

Abstract: Introduction: The gold-standard procedure to address malignant gastric outlet obstruction (MGOO) is surgical gastrojejunostomy (SGJJ). Two endoscopic alternatives have also been proposed: the endoscopic stenting (ES) and the endoscopic ultrasound-guided gastroenterostomy (EUS-G). This study aimed to perform a thorough and strict meta-analysis to compare EUS-G with the SGJJ and ES in treating patients with MGOO. Materials and Methods: Studies comparing EUS-G to endoscopic stenting or SGJJ for patients with MGOO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…In their retrospective study, Jaruvongvanich et al also showed that in a median observation duration of 185.5 days, EUS-GE in comparison with SGE was related with significantly increased clinical success rate (98.3% vs. 90.4%, p = 0.002), significantly lower reintervention rate for recurrent GOO (0.9%, and 13.7%, respectively, p < 0.0001) and lower adverse effects rate, indicating that EUS-GE could secure long-term patency and clinical improvement equally to SGE [36]. Furthermore, EUS-GE compared to SGE required a shorter post-procedure length of hospital stay (MD: -5.95; 95% CI: -6.99 to -4.91; p < 0.001; I2 = 95%) and led to faster return to both oral consumption and chemotherapy in cases of mGOO [35,37]. This is of great importance since these patients often have unresectable tumors and palliative chemotherapy is the only available therapy to improve their prognosis.…”
Section: Eus-ge Vs Sgementioning
confidence: 95%
“…In their retrospective study, Jaruvongvanich et al also showed that in a median observation duration of 185.5 days, EUS-GE in comparison with SGE was related with significantly increased clinical success rate (98.3% vs. 90.4%, p = 0.002), significantly lower reintervention rate for recurrent GOO (0.9%, and 13.7%, respectively, p < 0.0001) and lower adverse effects rate, indicating that EUS-GE could secure long-term patency and clinical improvement equally to SGE [36]. Furthermore, EUS-GE compared to SGE required a shorter post-procedure length of hospital stay (MD: -5.95; 95% CI: -6.99 to -4.91; p < 0.001; I2 = 95%) and led to faster return to both oral consumption and chemotherapy in cases of mGOO [35,37]. This is of great importance since these patients often have unresectable tumors and palliative chemotherapy is the only available therapy to improve their prognosis.…”
Section: Eus-ge Vs Sgementioning
confidence: 95%